The Influence of Shuttle-Shape Emodin Nanoparticles on the Streptococcus suis Biofilm - Wenya Ding; Wenya Ding; Jin Sun; He Lian; Changgeng Xu; Changgeng Xu; Xin Liu; Xin Liu; Sidi Zheng; Sidi Zheng; Dong Zhang; Xiaopeng Han; et al. (Frontiers Media S.A., 2018)
Biofilm is one of the most important physiological protective barriers of the Streptococcus suis (S. suis), and it is also one of the primary causes of hindrance to drug infiltration, reduction of bactericidal effects, and the development of antibiotic resistance. In order to intervene or eliminate S. suis biofilm, shuttle-shape emodin-loaded nanoparticles were developed in our study. The emodin nanoparticles were prepared by emodin and gelatin-cyclodextrin which was synthesized as drug carrier, and the nanoparticles were 174 nm in size, -4.64 mv in zeta potential, and exhibited a sustained emodin release. Moreover, the delivery kinetics of nanoparticles were also explored in our study. The confocal laser scanning microscopy and colony forming unit enumeration experiment indicated that nanoparticles could increase drug infiltration and uptake by biofilm. The flow cytometry system analysis showed that nanoparticles could be up taken by 99% of the bacteria cells. TCP assay and scanning electron microscopy showed that the nanoparticles had better effect on biofilm inhibition and elimination when compared with emodin solution. These results revealed that the emodin nanoparticles had a better therapeutic effect on the S. suis biofilm in vitro.